Barriers to women in using ICT for education and training in some developing countries - Quek, Ai Hwa; Faghiharam, Batoul (2008)
This paper addresses barriers to women in using ICT for education and training in some developing countries. For the purpose of this paper, reference is made to the developing countries in the Asia-Pacific region, where women received less attention in ICT usage for education and training. Notwithstanding the UNESCO declaration on "Education For All" some research studies indicate that women faced barriers in ICT usage, such as e-learning in these countries. In general, these barriers are grouped into social and non-social barriers. Examples of non-social barriers are constraints posed by family members, peers and customs. Examples of non-social barriers are difficult situations at home and in institutions of education and training that hinder women's usage of ICT. This paper also discusses some steps to overcome these barriers.